1985
DOI: 10.1002/ijc.2910350407
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of oestradiol in plasma from postmenopausal women with or without breast cancer: Relationships with metabolic clearance rates of oestradiol

Abstract: The distribution of oestradiol in plasma from postmenopausal women with or without breast cancer has been measured and related to the metabolic clearance rates of oestradiol (MCR-E2). All measurements were carried out preoperatively. No difference in the free fraction of oestradiol was found between women with breast cancer (1.8 +/- 0.4%, mean +/- SD) and normal women (1.6 +/- 0.3%). Approximately 40% of oestradiol in plasma was bound to albumin with 60% bound to sex hormone binding globulin (SHBG), but values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Siiteri's initial paper (31) reporting that free estradiol was elevated in postmenopausal breast cancer was followed by a number of similar case-control studies (21,26,30,(34)(35)(36)(37)(38)(39)(40)(41)(42). With some exceptions, (36,39,42) these studies appeared to confirm Siiteri's initial observations, but their overall impact was modest when it became evident that the observed association was not of sufficient strength to explain much of breast cancer epidemiology.…”
mentioning
confidence: 86%
“…Siiteri's initial paper (31) reporting that free estradiol was elevated in postmenopausal breast cancer was followed by a number of similar case-control studies (21,26,30,(34)(35)(36)(37)(38)(39)(40)(41)(42). With some exceptions, (36,39,42) these studies appeared to confirm Siiteri's initial observations, but their overall impact was modest when it became evident that the observed association was not of sufficient strength to explain much of breast cancer epidemiology.…”
mentioning
confidence: 86%
“…There is considerable evidence that increased serum estrogen levels are associated with an increased risk of breast cancer in postmenopausal women (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38); and increased urinary excretion rates of estrogen (estrone, estradiol and estriol conjugates) in postmenopausal breast cancer cases compared to controls have also been consistently found (39)(40)(41)(42)(43)(44)(45)(46). In addition to increased serum estrogen levels, it has also been suggested that the pathway by which estrone (El) is metabolized may be important in determining breast cancer risk (47)(48).…”
Section: Project 2a Estrogen Metabolism In Breast Cancer Cases and Cmentioning
confidence: 99%
“…In an attempt to determine changes in cases-controls could obscure or They injected 33 peri-and postmenopausal whether an elevated ratio of 16cx-to accentuate the differences between these breast cancer patients and 10 postmeno-2-hydroxylation precedes diagnosis, groups. We addressed this issue by asking pausal controls with E 2 tracers labeled with Osborne and co-workers used radiometric participants whether they have changed 3 H in the 17(c, C-2, and 16ct position, methods to study estrogen metabolism in their diet in the past 10 years, and we will They drew serial blood samples before premenopausal women presumed to be at include a complete analysis of these data in a and after isotope administration and high or low risk of breast cancer (34). subsequent report on the completed study.…”
Section: 0% Higher and The Mean 2-ohe 1 Was 3 Months Or Weighed Mormentioning
confidence: 99%